DEVELOPING ENGLISH LANGUAGE SKILLS THROUGH CRITICAL THINKING IN HIGHER EDUCATION - Abdirakhimova Mokhigul Normurodovna; Akhrorov Saidamin Sayfutdinovich; Mamadyokubova Ismigul Ural kizi; Jabborov Asilbek Jamshid ogli (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Annotation: This article explores the role of critical thinking in teaching English in  higher  education.  In  modern  education,  developing  students’  ability  to  analyze, evaluate, and interpret information is as important as acquiring language skills. The study  examines  how  integrating  critical  thinking  activities  into  English  language instruction enhances learners’ communicative competence and cognitive development. Particular attention is given to interactive methods such as debates, problem-solving tasks,  and  analytical  writing.  The  findings  suggest  that  critical  thinking-based instruction  significantly  improves  students’  engagement,  autonomy,  and  overall language proficiency.